The influence of sodium sulfate and magnesium sulfate on the stability of bound chlorides in cement paste. (20th December 2019) - Yang, Zhiqiang; Jiang, Jinyang; Jiang, Xing; Mu, Song; Wu, Meng; Sui, Shiyu; Wang, Liguo; Wang, Fengjuan
Highlights: Sulfate attack under three conditions. Parts of bound chlorides will be released due to sulfate attack. Cb is more advantageous than Rb for evaluating the chloride binding. The influence of MgSO4 attack on the stability of bound chlorides depends on the concentration of MgSO4 solution. Abstract: Chloride binding is an important factor for chloride transport in cementitious materials. The ions from the pore solution or the environment may affect the stability of the bound chlorides. In this study, the equilibrium method was used to investigate the stability of bound chlorides of well hydrated cement paste (HCP) with different concentrations of sodium sulfate (Na2 SO4 ) and magnesium sulfate (MgSO4 ) attack under three conditions (including: I. HCP intermixed with chloride was submerged in sulfate solution; II. HCP was soaked in combined chloride-sulfate solution; III: HCP was exposed to chloride solution, followed by sulfate solution). Experimental techniques including X-ray diffraction (XRD) and thermogravimetric (TG) were combined to identify the phase assemblage of HCP before and after sulfate attack. The results show that the presence of sulfate decreases the amount of bound chlorides, which is mainly caused by the decomposition of Friedel's salt. Besides, the influence of MgSO4 attack on the stability of bound chlorides depends on the concentration of MgSO4 solution. As a result of the "blocking effect" of brucite, sample exposed to 1% MgSO4 presented a higher chloride binding capacity than that exposed to 1% Na2 SO4 solution. However, extensive brucite and gypsum were formed with the increase of the concentration of MgSO4 solution. This leads to the formation of microcracks in cement paste, which provides additional routes for the ingress of sulfate ions.